1997
DOI: 10.1126/science.277.5323.197
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Lifetimes of Objects Injected into Asteroid Belt Resonances

Abstract: Numerical simulations of particles placed in orbital resonances in the main asteroid belt show that the typical dynamical lifetimes of objects that could become near-Earth asteroids or meteorites are only a few million years, with the majority destroyed by being transferred to Jupiter-crossing orbits or being driven into the sun. Particles that fortuitously migrate to the terrestrial planet region may be pushed to high-inclination orbits by resonances but are still dynamically eliminated on time scales of -10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

24
334
3
7

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 422 publications
(368 citation statements)
references
References 22 publications
24
334
3
7
Order By: Relevance
“…Sungrazing orbits are predicted to be a major end state of main-belt asteroids and near-Earth objects (Farinella et al 1994;Gladman et al 1997) but are yet to be observed. Models of solar system evolution predict the numbers and original source regions of small perihelion distance (q) objects and also expect such orbits to be common (Bottke et al 2002;Greenstreet et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Sungrazing orbits are predicted to be a major end state of main-belt asteroids and near-Earth objects (Farinella et al 1994;Gladman et al 1997) but are yet to be observed. Models of solar system evolution predict the numbers and original source regions of small perihelion distance (q) objects and also expect such orbits to be common (Bottke et al 2002;Greenstreet et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several groups (Gladman et al, 1997;Murray and Holman 1997;Migliorini et al, 1998, Morbidelli andNesvorný et al, 2002) have shown that mean-motion, three-body (Murray and Holman, 1997;Murray et al, 1998;Morbidelli, 1998, 1999), and secular resonances are capable of modifying proper the e and i among main-belt asteroids. The proper a is left unchanged by resonances (Murray and Dermott, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In a mean motion resonance such as that responsible for the 3/1 Kirkwood gap, the eccentricity of the resonant asteroid undergoes a random walk. Since the eccentricity cannot decrease below zero, there is a tendency for bodies with small e to drift to larger e. When the eccentricity is large enough, the asteroid strikes the Sun (Gladman et al 1997). A small fraction will su †er close encounters with the Earth or other terrestrial bodies ; this may lead to Jupiter crossing orbits, which usually leads to ejection of the asteroid from the solar system.…”
mentioning
confidence: 99%
“…This suggests that material has been removed from the gaps under the inÑuence of Jupiter. Over the last twenty years, the dynamics of this removal have been worked out in considerable detail (Wisdom 1983 ;Holman & Murray 1996 ;Gladman et al 1997). The gaps are the result of resonant, chaotic perturbations of the aster-FIG.…”
mentioning
confidence: 99%